1995
DOI: 10.1088/0953-8984/7/32/018
|View full text |Cite
|
Sign up to set email alerts
|

Landau Fermi-liquid theory for heavy-fermion compounds. I. Thermodynamics

Abstract: We generalize the Landau Fermi-liquid theory for describing electrons in heavyfermion compounds. The theory gives resuIts in good agreement with microscopic mean-field approaches. We study the low-temperamre magnetic properties of the compounds and the competition between ferromagnetism and the coherent Kondo state, taking into a m u t the RKKY interaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1996
1996
1996
1996

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…In the present paper we derive a description of dynamic phenomena in heavy-fermion compounds within the generalized Landau Fermi-liquid theory proposed in our previous paper [11] where we have shown that the phenomenological approach gives a detailed description of the low-temperature thermodynamic properties of the heavy-fermion ground state in agreement with microscopic approaches [8,9]. Moreover the Landau-like approach has enabled us to study the ferromagnetic phase transition stimulated by the RKKY interaction.…”
Section: Introductionmentioning
confidence: 73%
See 4 more Smart Citations
“…In the present paper we derive a description of dynamic phenomena in heavy-fermion compounds within the generalized Landau Fermi-liquid theory proposed in our previous paper [11] where we have shown that the phenomenological approach gives a detailed description of the low-temperature thermodynamic properties of the heavy-fermion ground state in agreement with microscopic approaches [8,9]. Moreover the Landau-like approach has enabled us to study the ferromagnetic phase transition stimulated by the RKKY interaction.…”
Section: Introductionmentioning
confidence: 73%
“…It is important to note that in the general case the local effective energy of f electrons (ε f (r, t) = εf +ε f 1 (r, t)) depends on r and t. In accordance with the Landau-like approach to heavy fermion systems [11] the value of ε f (r, t) is determined by the constraint that the number N f of f electrons does not depend on r and t in low-frequency processes, i.e.…”
Section: Kinetic Equationmentioning
confidence: 80%
See 3 more Smart Citations